Mapping Electrical Impedance Spectra of the Healthy Oral Mucosa: a Pilot Study - Ivica Richter; Ivan Alajbeg; Vanja VUČIĆEVIĆ BORAS; Ana ANDABAK ROGULJ; Vlaho Brailo (University of Zagreb. School of Dental Medicine, 2015)
Objective: Electrical impedance is the resistance to the electric current flow through a tissue and depends on the tissue's structure and chemical composition. The aim of this study was to map electrical impedance spectra for each region of the healthy oral mucosa. Materials and Methods: Electrical impedance was measured in 30 participants with healthy oral mucosa. Measurements were performed in 14 points on the right and the left side of the oral cavity, and repeated after 7 and 14 days respectively. Results: The lowest values were measured on the tongue dorsum and the highest values were measured on the hard palate. No significant differences were found between the right and the left side. Significantly higher values were found in females on the upper labial mucosa, tongue dorsum and the ventral tongue. Significant difference between smokers and non-smokers on the lower labial mucosa and floor of the mouth was found. Electrical impedance was negatively correlated with salivary flow on the upper labial mucosa, hard palate, tongue dorsum and sublingual mucosa. Higher variability of measurements was found at low frequencies. Conclusions: Electrical impedance mostly depends on the degree of mucosal keratinization. Demographic and clinical factors probably affect its values. Further studies with bigger number of participants are required.